Reinforcement of stent materials using nanoparticles - Ng, Soon Ping. (2008)
To look at the effects of addition of bioactive HA particles on the mechanical strengthening of the cast film. To study the dispersion of the particles in the polymer matrix. To compare the effect of nanofillers with micronfillers on the mechanical performance of composite films.